"No One Who Has a Blemish Shall Draw Near": Pentecostals Rising Above a Disabling Hermeneutics. (2nd April 2016) - Nkomazana, Fidelis
Abstract: The article examines the challenges faced by the Pentecostal churches in practically and sensitively interpreting Biblical texts that relate to disabilities. It challenges the perception of Pentecostals regarding disability, especially in the context of their doctrines, teaching and general practices and beliefs. It shows how the Pentecostals have long struggled with those Biblical texts that portray disabilities negatively. It also appreciates that Pentecostals have at times positively used the healing narratives and miracles of Jesus and his disciples to emphasize the importance of physical healing, without marginalizing people with disabilities in the church and society. The article particularly uses Pentecostal churches in Botswana as examples of how Pentecostals worldwide have handled the issue of disability.